Systematic literature review: Analysis of the borobudur temple model on the beliefs of the nation's children: I Ketut Damana - Damana, I Ketut (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
Borobudur chatra as an integral part of the architecture and symbolism of Borobudur Temple has a deep philosophical meaning in the culture and beliefs of the Indonesian people. This study aims to analyze the relationship between the Borobudur chatra model and the formation and strengthening of national belief values through a systematic literature review (SLR) approach. The research process was carried out by identifying, evaluating, and synthesizing relevant literature from various academic sources. This study reveals that chatra represents protection, sanctity, and the relationship between humans and the universe. This symbolic meaning plays an important role in shaping spiritual values, cultural pride, and the identity of the nation's children. The results of the study indicate that Borobudur chatra is not only a spiritual symbol, but also a tool to educate the younger generation about the importance of local cultural values in modern life. This study suggests the need for integration of Borobudur symbolism in the education curriculum to strengthen the sense of trust and cultural pride in the nation's children.